ALIH FUNGSI LAHAN PERTANIAN DAN DAMPAKNYA TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA SEMBALUN LOMBOK TIMUR - Pila Agustina (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2022)
This study aims to explain the socio-economic impact of the Sembalun Bumbung village community after converting agricultural land. This study uses qualitative research with a phenomenological approach. The results showed that several factors influence the conversion of agricultural land, namely economic factors, strategic location, treatment costs (expensive drugs), occupation, and socio-culture. The socio-economic impact of the Sembalun Bumbung village community after the conversion of agricultural land has increased, seen from the income per individual when farming an average of 5-8 million per harvest, while the payment after the conversion of agricultural land is 12-15 million/month.